2020
DOI: 10.1590/1809-2950/19028627032020
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência de discinese escapular e dor no ombro em surfistas amadores do Rio Grande do Sul: um estudo transversal

Abstract: RESUMO O movimento de remada representa 51,4% do tempo total de prática do surfe, gerando alta demanda muscular do complexo do ombro. Apesar disso, há uma lacuna na literatura sobre a prevalência de dor e discinese escapular (DE) em surfistas. Este estudo teve o objetivo de avaliar a prevalência de dor no ombro em surfistas amadores do estado do Rio Grande do Sul, no Brasil. Trata-se de estudo observacional descritivo transversal. Foram incluídos 21 homens, com idade entre 18 e 42 anos, que praticassem surfe h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
2
0
1
Order By: Relevance
“… 5 Sports including baseball, tennis, swimming, volleyball, cricket, kayaking, and surfing have demonstrated an incidence of 30%-70% dyskinesis. 13 , 16 , 30 , 39 , 40 , 49 , 54 Studies in symptomatic patients reveal an incidence between 64%-100% depending on the anatomic diagnosis. 14 , 21 , 27 , 28 , 35 , 43 , 59 The literature has also shown that an increased risk of shoulder pain and injury exists when scapular dyskinesis is present.…”
mentioning
confidence: 99%
“… 5 Sports including baseball, tennis, swimming, volleyball, cricket, kayaking, and surfing have demonstrated an incidence of 30%-70% dyskinesis. 13 , 16 , 30 , 39 , 40 , 49 , 54 Studies in symptomatic patients reveal an incidence between 64%-100% depending on the anatomic diagnosis. 14 , 21 , 27 , 28 , 35 , 43 , 59 The literature has also shown that an increased risk of shoulder pain and injury exists when scapular dyskinesis is present.…”
mentioning
confidence: 99%
“…A discinesia escapular também é um achado frequente nos pacientes com queixa de dor no ombro. Estudos recentes realizados com indivíduos comuns, praticantes de atividades físicas habituais e/ou de algum esporte na categoria amador demonstraram que a vasta maioria dos pacientes com queixas de dor na articulação do ombro apresentam algum grau de comprometimento do ritmo escapuloumeral [16,[26][27][28] . O presente estudo vai ao encontro dessas informações.…”
Section: Discussionunclassified
“…7.11 Scapular kinematicsScapular kinematics, dyskinesis and EMG studies of the scapular stabilizers were performed by the following authors:[30, 48, 61, 76, 84, 86,[88][89][95][96][97]. The results are highlighted, discussed and tabularized in the "SoF" section (Online Resource I) and in the "Table of Characteristics" section (Online Resource 2).…”
mentioning
confidence: 99%